Drone‐based physiological index reveals long‐term acclimation and drought stress responses in trees. (14th September 2021) - D'Odorico, Petra; Schönbeck, Leonie; Vitali, Valentina; Meusburger, Katrin; Schaub, Marcus; Ginzler, Christian; Zweifel, Roman; Velasco, Vera Marjorie Elauria; Gisler, Jonas; Gessler, Arthur; Ensminger, Ingo
Abstract: Monitoring early tree physiological responses to drought is key to understanding progressive impacts of drought on forests and identifying resilient species. We combined drone‐based multispectral remote sensing with measurements of tree physiology and environmental parameters over two growing seasons in a 100‐y‐old Pinus sylvestris forest subject to 17‐y of precipitation manipulation. Our goal was to determine if drone‐based photochemical reflectance index (PRI) captures tree drought stress responses and whether responses are affected by long‐term acclimation. PRI detects changes in xanthophyll cycle pigment dynamics, which reflect increases in photoprotective non‐photochemical quenching activity resulting from drought‐induced photosynthesis downregulation. Here, PRI of never‐irrigated trees was up to 10 times lower (higher stress) than PRI of irrigated trees. Long‐term acclimation to experimental treatment, however, influenced the seasonal relationship between PRI and soil water availability. PRI also captured diurnal decreases in photochemical efficiency, driven by vapour pressure deficit. Interestingly, 5 years after irrigation was stopped for a subset of the irrigated trees, a positive legacy effect persisted, with lower stress responses (higher PRI) compared with never‐irrigated trees. This study demonstrates the ability of remotely sensed PRI to scale tree physiological responses to an entire forest and the importance of long‐term acclimation in determining current drought stress responses. Abstract : Drone‐based Photochemical Reflectance Index (PRI) captured Pinus sylvestris responses to drought in a long‐term (17‐year) precipitation manipulation (irrigation) experiment. Tree responses were found dependent on acclimation to past environmental conditions and derived legacy effects.